Zur Anlockung von Staphyliniden durch chemische Substanzen (Vorläufige Mitteilung). - Gottschalk, Cord (Contributions to Entomology = Beiträge zur Entomologie, 1958)
By means of a simple trap there was found an attractive agency in Anthobium primulae Steph. caused by Anethol and in Megaloscapa punctipennis Kr. caused by Octylalcohol. The biological significance of both the attractive agents mentioned is to be studied in the course of further experiments.